Analysis Of The Legal Position Of Cctv As Evidence In Criminal Cases (STUDY OF Decision Number 8/PID.SUS-ANAK/2021/PT-PDG) - Ridwan Ridwan; Kusno Kusno; Ahmad Ansyari Siregar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study is intended to find out and understand the legal position of CCTV as evidence in criminal cases (Decision Study). Number 8/Pid.Sus-Anak/2021/PT-Pdg). This study uses a normative legal research method. Normative legal research is examining law from an internal perspective with the object of research being legal norms. Discussion results: CCTV has the same position as other evidence regulated and stipulated in the Criminal Procedure Code. Because its position is the same as other evidence, CCTV is considered to have the same legal force as SUCH evidence. Although not explicitly stated in the Criminal Procedure Code, CCTV can be used as additional or evidence as further evidence in a criminal case. However, there are provisions that require that there must be a relationship between one piece of evidence and another